A Distributed Multiplayer Game to Promote Active Transport at Workplaces: User-Centered Design, Implementation, and Lessons Learned - Laine, Teemu H.; Normark, Jorgen; Lindvall, Helena; Lindqvist, Anna Karin; Rutberg, Stina (IEEE Transactions on Games, 2020)
Recent decline in active transport and increase in motorized transport decreases physical activity and increases air pollution. Using games to motivate people to change their behavior toward active transport can mitigate this. We proposed Tic-Tac-Training, a distributed, collaborative, and competitive game for promoting active transport at workplaces. Tic-Tac-Training was developed through a multidisciplinary and iterative user-centered design (UCD) process in four stages: 1) paper prototype, 2) low-fidelity prototypes, 3) high-fidelity prototypes, and 4) digital prototype. User testing and playtesting (N = 12) yielded a number of improvement suggestions. We also analyzed how Tic-Tac-Training supports the eight core drives of gamification (Octalysis), and presented 17 lessons learned in four categories. Findings suggest that UCD can be useful for developing exergame interventions for workplaces. Moreover, the lessons learned can benefit exergame designers. More research is needed to measure the behavior change effect of Tic-Tac-Training and its applicability to other use cases.
Keywords: Active transport; Behaviour changes; Competitive games; Digital prototype; Distributed multi-player games; Low fidelities; Paper prototypes; Physical activity; Active transport; exergame; gamification; physical activity; user-centered design (UCD)